2023
DOI: 10.1039/d2sc04707a
|View full text |Cite
|
Sign up to set email alerts
|

The anti-breast cancer stem cell properties of gold(i)-non-steroidal anti-inflammatory drug complexes

Abstract: The anti-breast cancer stem cell (CSC) properties of a series of gold(I) complexes comprising of various non-steroidal anti-inflammatory drugs (NSAIDs) and triphenylphosphine 1-8 are reported. The most effective gold(I)-NSAID complex...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 76 publications
1
12
0
Order By: Relevance
“…392 Suntharalingam and co-workers developed gold(I) complexes bearing nonsteroidal anti-inflammatory drugs (NSAID) to target breast cancer stem-cells (Figure 24). 393 Lead complex containing indomethacin moiety showed greater inhibitory effect (80-fold) against breast CSCs than the bulk breast cancer cell population. An inquiry into the mechanism of action of the lead complex revealed cytoplasmic accumulation of the complex, inhibition of cyclooxygenase-2 (COX-2) and increased levels of intracellular ROS.…”
Section: Mitochondrial Targeting Of Gold Complexesmentioning
confidence: 99%
See 3 more Smart Citations
“…392 Suntharalingam and co-workers developed gold(I) complexes bearing nonsteroidal anti-inflammatory drugs (NSAID) to target breast cancer stem-cells (Figure 24). 393 Lead complex containing indomethacin moiety showed greater inhibitory effect (80-fold) against breast CSCs than the bulk breast cancer cell population. An inquiry into the mechanism of action of the lead complex revealed cytoplasmic accumulation of the complex, inhibition of cyclooxygenase-2 (COX-2) and increased levels of intracellular ROS.…”
Section: Mitochondrial Targeting Of Gold Complexesmentioning
confidence: 99%
“…This work further demonstrates that targeting CSCs is an effective strategy for cancer treatment. 393 Sun et al also reported a gold(III) meso-tetraphenylporphyrin complex that inhibit formation of spheroids from single cell suspension in U-87 glioblastoma cancer cells. The porphyrin complex demonstrated potent in vitro and in vivo toxicity in a panel of cancer cells and high physiological stability in glutathione and serum albumen.…”
Section: Mitochondrial Targeting Of Gold Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…A more recent study demonstrated a multitarget nature of the alkynyl phosphane gold­(I) complex by disrupting mitochondrial bioenergetics and glycolysis . Endeavors of using other donor ligands with dual or synergistic activities also emerged recently. …”
Section: Concept In Gold Drug Designmentioning
confidence: 99%